Effect Of 4-weeks Traditional Archery Intervention On Hand-eye Coordination And Upper Limb Reaction Time Among Sedentary Youth - Mohd Azrul Anuar Zolkafi; Hayati Abdul Rahman; Noor Aien Mon Sarip; Nur Islami Teng Abdullah; Mohd Azmani Sahar; Norsham Juliana Nordin (Academic Research Publishing Group, 2024)
The Journal of Social Sciences Research ISSN(e): 2411-9458, ISSN(p): 2413-6670 Special Issue. 6, pp: 1225-1230, 2018